New Approach for Intelligent Street Lights Using Computer Vision and Wireless Sensor Networks - Yaman, Orhan; Karakose, Mehmet (Ieee, 2019)
Smart city is expressed in many different ways by people today. In recent years, smart cities and green technology have become one of the most important and promising items on the world agenda to prepare a better future. The concept of smart city has received great interest in the context of urban development policies. The goal of a smart city is to better use public resources while improving the quality of services provided to citizens while reducing the operational costs of public administration. In this study, wireless sensor networks for smart cities are developed based on smart street light applications. The street lights are equipped with wireless sensor kits to monitor the temperature, humidity and carbon dioxide information of the environment and to monitor the changes in the regions. In addition, the mobility of the environment is analyzed with the camera attached to each sensor kit. The sensor kit was developed using Raspberry pi programming card. A sensor kit for this card has been developed. A wireless sensor network has been created by adding Xbee wireless modules on the sensor kit. The obtained data is collected in a database. The collected data is displayed to the user through an interface.
7th International Istanbul Smart Grids and Cities Congress and Fair (ICSG) -- APR 25-26, 2019 -- Istanbul, TURKEY
Keywords: Computer vision; Embedded software; Sensors; Smart devices; Wireless sensor networks